Forager : field notes for surviving a family cult - Dowd, Michelle, 1968- (Algonquin Books of Chapel Hill, 2023)
"Michelle Dowd grew up on a mountain in the Angeles National Forest, born into an ultra-religious cult--the Field, as members called it--run by her grandfather, who believed that his chosen followers must prepare themselves to survive doomsday. Bound by the group's patriarchal rules and literal interpretation of the Bible, Michelle and her siblings lived a life of deprivation, isolated from Outsiders and starved for both love and food. She was forced to learn the skills necessary to battle hunger, thirst, and cold; she learned to trust animals more than humans; and most important, she learned how to survive by foraging for what she needed. And as Michelle got older, she realized she had the strength to break free. Focus on what will sustain, not satiate you, she would tell herself. Use everything. Waste nothing. Get to know the intricacies of the land like the intricacies of your body. And so she did." -- inside front jacket flap.